Effect of dynamic high-pressure treatment on the interfacial and foaming properties of soy protein isolate-hydroxypropylmethylcelluloses systems - Martínez, Karina Dafne (2010)
The objective of the work was to study the effect of dynamic high-pressure homogenization (HPH) on the interfacial and foaming properties of soy protein isolate (SP) and surface-active polysaccharides (E4M and E15) with different molecular weight. SP was dispersed with water (2% w/v) together with the polysaccharides (0.3% w/v) and subjected to high-pressure from 0 to 300 MPa, in 100 MPa intervals. After treatment, foam overrun by whipping method, viscosity, particle size distribution and surface pressure at 48 s of drop formation time, of systems were measured. The effect of HPH of these systems on foam overrun was not directly relation with the effect on the surface pressure at short adsorption time. The viscosity decrease may be explained some of the foaming results together with interfacial performance at longer adsorption time than 48 s which depend on the system and level of pressure applied. According to the polysaccharide used in this work, interactions between SP and polysaccharides apparently favour the foam overrun on untreated mixed systems; this effect was promoted using HPH particularly in the case of E15 at 300 MPa. The effect of SP–E4M was less pronounced from the one observed for E15. Thus, the molecular weight of polysaccharides is a very important factor of interaction with soy protein isolate under these conditions of high-pressure homogenization.